Biological action in Read–Write genome evolution. Issue 5 (18th August 2017) - Shapiro, James A.
Abstract : Many of the most important evolutionary variations that generated phenotypic adaptations and originated novel taxa resulted from complex cellular activities affecting genome content and expression. These activities included (i) the symbiogenetic cell merger that produced the mitochondrion-bearing ancestor of all extant eukaryotes, (ii) symbiogenetic cell mergers that produced chloroplast-bearing ancestors of photosynthetic eukaryotes, and (iii) interspecific hybridizations and genome doublings that generated new species and adaptive radiations of higher plants and animals. Adaptive variations also involved horizontal DNA transfers and natural genetic engineering by mobile DNA elements to rewire regulatory networks, such as those essential to viviparous reproduction in mammals. In the most highly evolved multicellular organisms, biological complexity scales with 'non-coding' DNA content rather than with protein-coding capacity in the genome. Coincidentally, 'non-coding' RNAs rich in repetitive mobile DNA sequences function as key regulators of complex adaptive phenotypes, such as stem cell pluripotency. The intersections of cell fusion activities, horizontal DNA transfers and natural genetic engineering of Read–Write genomes provide a rich molecular and biological foundation for understanding how ecological disruptions can stimulate productive, often abrupt, evolutionary transformations.